MEDIA PEMBELAJARAN FISIKA SMA BERBASIS VIDEO PADA POKOK BAHASAN MOMENTUM, IMPULS DAN TUMBUKAN - Hingkua, Patris Fernandes (Jurnal Pendidikan Fisika-WM, 2014)
Visualization is very essential in physics learning, especially on the topics of momentum, impulse, and collisions. This is mainly due to the instantaneous process of collision that makes it difficult to be observed directly. Video-based learning media is one of the alternative media that can be used to present the visualization of physics learning material on that topic. This research aimed to develop video-based learning media for high school physics learning on the topics of momentum, impulse, and collision which was equipped with experiment and computer animation. The method applied in this research was the research and development method aiming at the learning media production. The research procedures consisted of field observations, research problem, preparation and development of the learning media, expert judgement, then followed by tryout of the developed learning media by high school students. The results of the research showed that the developed learning media satisfied the research goal; 83,33% of the learning media users participating in the tryout stated that the media is good.